Security Issues In Shared Key Authentication on IEEE 802.11 Wireless Standards and UUM Wireless Network. - El Omari, Abdullah Abdelmonem M. (2007)
The explosive growth on wireless network over the world is increased but that does not mean it is a flawless kind of technology. One of these flows or problems is the unsecured issue on 802.11 wireless standard which is authentication mechanism. Organization usually use for secure internal resource and infrastructure from attacker internet firewall. The experts believe that Access Points (AP'S) present a large number of problems; unauthorized use and access to internal data. On the other hand, one cannot ignore the truth that the AP can provide several security mechanisms. Therefore, this study aims to present the best solution to AP security problem to make it as secure as possible. The result of this study depends on a scrutinized reading for other works and personal overview that are built on academic and scientific theories. This logical solution can be summarized as the following: by increasing the number of users on wireless networks it going to be vulnerable to unauthorized use or access to their internal infrastructure, by taking the guideline can make the communications betweens client and AP more secure as possible.